PRINSIP-PRINSIP MANAJEMEN PENDIDIKAN VS KINERJA GURU: SEBUAH TINJAUAN UMUM - Sola, Ermi (Department of Islamic Education Management, 2021)
Abstract: Principles of Education Management VS Teacher Performance Management: an OverviewThe quality of education in each school is different. This happens because of different managerial strategies in managing school resources. Educational management is a series of activities carried out by a group of people who are members of educational organizations, to achieve predetermined educational goals, by utilizing existing resources and using management functions to achieve goals effectively and efficiently. The quality of the education and learning process can be viewed from two aspects, namely the quality of the components and the quality of school management. Although the supporting components such as the availability of adequate facilities and infrastructure, and sufficient funds, if they are not managed